Detection of Protozoa in Drinking Water of Kathmandu Valley, Nepal - Sah, Siyaram Prasad; Pradhan, Bijay Lal; Prasad, Archana (Patan Prospective Journal, 2024)
Introduction: Safe drinking water is a delicate matter, and its quality needs to be periodically checked. Although there has been microbial research on drinking water protozoan occurrence is uncommon in Nepal. The goal of the current study was to analyze the readily evaluable biological examination of tap water, tube well water and dug well water sources in the Kathmandu Valley of Nepal. Methodology: A total of 720 samples were collected from residential colonies of Baneshwor, Chhetrapati, Bansbari, and Tripureshwor areas in the Kathmandu Valley of Nepal. The sample were collected in 2021 across the four seasons, spring (March-May), summer (June-August), autumn (September-November) and winter (December-February). To collect the drinking water samples, sterilized bottles with the capacity of 1000 ml were used and capped tightly. The Centrifugation method was employed for the identification of protozoa by routine parasitology with a light microscope. Results: The major protozoa found in Nepal are Giardia lamblia, Entamoeba histolytica, Amoeba proteus, which are directly contaminated with fecal matter. The total number of positive cases reported was 42 (5.83%), from the tap water samples, there were the total five positive cases 5 (0.69%) in which 5 species were identified as non-pathogenic and 1 species as pathogenic. In the tube well samples total number of 11 protozoa were detected 11 (1.52%) in which 9 species were non-pathogenic, and two species were pathogenic. Among dug well water samples, there were 26 positive cases (3.61%), where 34 species were identified as non-pathogenic and 12 species as pathogenic. Amoeba proteus 32 (4.44%), Paramecium caudatum 24 (3.33%), Giardia lamblia, 8 (1.11%) Entamoeba histolytica 6 (0.83%) and Balantidium coli 1(0.13%). Chi square test suggests that there is no significant difference of positive samples among different locations (Chi-square = 0.30341, df = 3, p-value=0.9594). The similar test among seasons indicates significant difference (Chi-square = 6.574, p-value=0.086). However notable significant difference was found in different types of water (tape water, tube-well water, and dug-well water) Chi-square = 17.75, df = 2, p-value = 0.00013990. Interpretation: Overall, the number of positive cases was more in summer than other seasons which could be due to obnoxious contamination of rainwater in drinking water.